A new myrmecophilous Allochernes (Arachnida: Pseudoscorpiones: Chernetidae) from Catalunya, Spain - Henderickx, Hans; Vets, Vik (Zootaxa, 2003)
Allochernes deceuninckorum sp.n., a new myrmecophilous pseudoscorpion from Catalunya, Spain, is described.